Utvärdering av en joystickstyrd robotarms noggrannhet och repeterbarhet Vid placering av acetabularkopp för total höftledsartroplastik - Bellander, Isabelle; Haque, Omeya; Jansson, Anton; Sahan, Bedirhan; Wrångemyr, Elsa (My University, 2026)
In total hip replacement surgery, the correct positioning and orientation of the acetabular cup, one of the components of the hip prosthesis, is crucial to avoid complications. Conventionally, the placement of the acetabular cup is performed manually by the surgeon, which places high demands on precision and experience; however, with technical aids such as robot-assisted surgery and navigation systems, it is possible to reduce the human factor at critical moments. Thus, the work investigates the position accuracy and repeatability of a joystick-controlled robot arm when steering towards a defined target point. Through experimental and virtual tests, the robot’s properties were simulated and analyzed. The results show that the joystick-controlled robot achieves position accuracy and repeatability within clinical error margins, with programmed movements providing the highest repeatability, while joystick control in combination with a navigation system is sufficiently reliable. The observed deviations are mainly attributed to geometric variations in the 3D-printed tool rather than the robot’s mechanics, which means that the accuracy can be improved through calibration. Future work should focus on improved calibration, more robust tool design, and further integration with clinical systems to enable safe and practical application in real-world surgical settings